Contending visions of the Middle East : the history and politics of Orientalism - Lockman, Zachary (Contemporary Middle East ;, 2004)
The book offers a survey of Western knowledge about Islam and the Middle East, from conceptions of East and West in antiquity, through the emergence of Islam, to the present. It relates many of today's critical issues, including terrorism and Muslim extremism, to their broader historical and political contexts.